SISTEM PEMBELAJARAN TAHFIZ AL-QUR’AN DENGAN METODE SAMĀ‘I DI PPTQ MISBAHUNNUR CIMAHI - Fujiyanti Nurlatifah; Fajar Syarif (Jurnal Al-Fatih, 2021)
This study discusses the process of learning tahfiz with the Samā‘i method applied at PPTQ Misbahunnur Cimahi, as we already know that in learning tahfiz Al-Qur'an a method is certainly needed to be applied to achieve the learning objectives, the purpose of this research is to describe the factual conditions of the object under study related to data and information about the process of learning tahfiz Al-Qur'an with the Samā‘i method applied in the pesantren. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques in this study were non-participatory observation, interviews and documentation. The data analysis technique in this study uses the theory of Miles and Huberman. The results of this study indicate that, in the process of learning tahfiz Al-Qur'an at PPTQ Misbahunnur it is carried out longer than other programs, the method used is a combination of Samā‘i , talaqqi, and tasmi methods. especially in online learning.